REALITAS PENGAKUAN HUKUM TERHADAP HAK ATAS MEREK SEBAGAI JAMINAN FIDUSIA PADA PRAKTIK PERBANKAN DI INDONESIA - Sri Mulyani (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2014)
This study describes the reality of the legal recognition of the rights to the brand as a fiduciary to the practice of banking in Indonesia. Mark rights have not been fully accepted as a fiduciary. Barriers mark rights have not been fully recognized as a fiduciary can be grouped within a factor of law and non-law. Legal factors refer to the lack of legal basis that can be used as a reference for the acceptance of the rights to the brand as a fiduciary. While the non-legal factors relating to the economic aspects in which the nature of the rights to the brand can not be predicted, so the bank's difficulties in measuring the economic value of the brand, because not all brands have economic value.